Gliricidia sepium for field and garden - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Chris Kakunta visits Harrison Chongwe, an innovative farmer who is using Gliricidia sepium instead of chemical fertilizer, with excellent results.